Side lengths of pseudoconvex fullerene patches - Graves, Christina M. (Ars mathematica contemporanea, 2012)
In this paper we consider fullerene patches with nice boundaries containing between one and five pentagonal faces. We find necessary conditions for the side lengths of such patches, and then prove these conditions are sufficient by constructing such patches.
Keywords: boundary codes; fulereni; fullerene patches; fullerenes; graph theory; pseudoconvex patches; teorija grafov